2013
DOI: 10.1159/000356213
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependency of Successful Recanalization in Anterior Circulation Stroke: The ENDOSTROKE Study

Abstract: Background: Clinical outcome after endovascular stroke therapy (EVT) for proximal anterior circulation stroke is often disappointing despite high recanalization rates. The ENDOSTROKE study aims to determine predictors of clinical outcome in patients undergoing EVT. Here we focus on the impact of age and recanalization on proximal middle cerebral artery (M1-MCA) or carotid T occlusion. Methods: ENDOSTROKE is an investigator-initiated, industrially independent multicenter registry launched in January, 2011, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
64
3
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 24 publications
13
64
3
2
Order By: Relevance
“…Additionally, in our study, there was no difference in intracranial hemorrhage rates of all types in the younger age group (19% versus 14%, P ϭ .410); moreover, hemorrhage did not have a significant impact on differences in clinical outcome or mortality rates between the 2 groups and is in keeping with previously published results. 12 Singer et al 22 demonstrated the highest rates of good clinical outcome (mRS Յ2) in the youngest quartile (60%) and the lowest in the oldest quartile (17%). They then dichotomized the entire patient cohort into good and poor clinical outcomes and determined the proportion of patients within each group in whom successful reperfusion was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in our study, there was no difference in intracranial hemorrhage rates of all types in the younger age group (19% versus 14%, P ϭ .410); moreover, hemorrhage did not have a significant impact on differences in clinical outcome or mortality rates between the 2 groups and is in keeping with previously published results. 12 Singer et al 22 demonstrated the highest rates of good clinical outcome (mRS Յ2) in the youngest quartile (60%) and the lowest in the oldest quartile (17%). They then dichotomized the entire patient cohort into good and poor clinical outcomes and determined the proportion of patients within each group in whom successful reperfusion was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…21 Intracranial hemorrhage was reported with the European Cooperative Acute Stroke Study classification. 22 For the current study, we excluded patients from both studies for whom no TICI score or 90-day mRS was available.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Previous studies with stent retrievers in patients older than 80 years include Gratz et al [7], who studied 50 octogenarian patients with anterior circulation strokes treated exclusively with Solitaire FR, with a recanalization rate of 74 %, mRS C 3 at 3 months of 89 %, and mortality of 44 %. Other articles analyzed the general impact of age in the clinical response to mechanical thrombectomy [20][21][22], but these papers did not focus on the subgroup of octogenarians and included other mechanical therapies different to stent-retrievers. Our series differ from Gratz's in that both patients with anterior and posterior circulation strokes have been included and up to four different stent-retrievers (not only Solitaire FR) could be chosen for treatment by the neurointerventionist in charge.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show increasing age correlation with unfavourable outcomes [21,26,27] with lower rates of recanalization [19] and higher mortality and haemorrhage [28] …”
Section: Discussionmentioning
confidence: 99%
“…Even when adjusted for recanalization, this age group displayed poorer clinical outcomes, with a trend of better outcomes with decreasing patient age [20,21].…”
Section: Introductionmentioning
confidence: 90%